The Solution of Two-Point Boundary Value Problem of a Class of Duffing-Type Systems with Non-C1 Perturbation Term. (19th August 2009) - Zhengxian, Jiang; Wenhua, Huang
Abstract : This paper deals with a two-point boundary value problem of a class of Duffing-type systems with non-C 1 perturbation term. Several existence and uniqueness theorems were presented.